The grounding of positive philosophy : the Berlin lectures - Schelling, Friedrich Wilhelm Joseph von, 1775-1854 (SUNY series in contemporary continental philosophy., 2007)
"The Berlin lectures in The Grounding of Positive Philosophy, appearing here for the first time in English, advance Schelling's final "existential system" as an alternative to modernity's reduction of philosophy to a purely formal science of reason. The onetime protege of Fichte and benefactor of Hegel, Schelling accuses German Idealism of dealing "with the world of lived experience just as a surgeon who promises to cure your ailing leg by amputating it." Schelling's appeal in Berlin for a positive, existential philosophy found an interested audience in Kierkegaard, Engels, Feuerbach, Marx, and Bakunin. The Berlin lectures provide insight into the thought processes of one of the most provocative yet least understood thinkers of nineteenth-century German philosophy."--Jacket